Highly Aligned Array of Heterostructured Polyflourene-Isolated Boron Nitride and Carbon Nanotubes - Yu, Ilhwan; Jo, Yerin; Ko, Jaehyoung; Moon, Se Youn; Ahn, Seokhoon; Joo, Yongho (American Chemical Society, 2021)
Boron nitride nanotubes (BNNTs) have attracted increasing attention for their exceptional thermal, electronic, and optical properties. However, the progress in BNNTs applications has largely been limited by the low purity of as-synthesized BNNTs and inefficient solution-processing protocols due mainly to the instability of BNNTs in most of the solvents. Therefore, fabrication of highly pure, stable, and fully individualized BNNTs in a rational manner is required. Here, we report a significant improvement in the preparation of well-dispersed BNNTs, utilizing conjugated polymers that interact with BNNTs, allowing selective sorting and individualization of the nanotubes. Evidence of strong interactions between the polymers and BNNTs was observed by optical absorption and photoluminescence spectroscopies, while effective individualization was observed by electron microscopy. The sorted BNNTs were successfully used in a solution-processing protocol called dose-controlled, floating evaporative self-assembly (DFES) previously established for single-walled carbon nanotubes (SWCNT) array fabrication. A device fabricated via DFES from the sorted BNNTs mixed with polymer-wrapped, semiconducting single-walled carbon nanotubes (s-SWCNTs) exhibited an on-state conductance of 253 +/- 6 mu S mu m(-1) and an on/off ratio of 106.6 +/- 0.4 for a gate voltage of -0.1 V. This breakthrough in BNNT dispersion and isolation is a significant advancement toward the exploitation of BNNTs in future applications.